Heterogeneous Firms, "Profit Shifting" FDI and International Tax Competition - Sebastian Krautheim; Tim Schmidt-Eisenlohr (Verein für Socialpolitik, 2010)
Larger firms are more likely to use tax haven operations to exploit international tax differences. We study a tax game between a large country and a tax haven modeling heterogeneous monopolistic firms, which can shift profits abroad. We show that a higher degree of firm heterogeneity (a mean-preserving spread of the cost distribution) increases the degree of tax competition, i.e. it decreases the equilibrium tax rate of the large country, leads to higher outflows of its tax base and thus decreases its equilibrium tax revenue. Similar effects hold for a higher substitutability across varieties. We find that models with homogeneous firms understate the strength of tax competition.
Keywords: F23; H25; H87; 330; heterogeneous firms; tax competition; profit shifting; tax havens